Modelization of the regulation of protein synthesis following fertilization in sea urchin shows requirement of two processes: a destabilization of eIF4E:4E-BP complex and a great stimulation of the 4E-BP-degradation mechanism, both rapamycin-sensitive - Laurent, Sébastien; Richard, Adrien; Mulner-Lorillon, Odile; Morales, Julia; Flament, Didier; Glippa, Virginie; Bourdon, Jérémie; Gosselin, Pauline; Siegel, Anne; Cormier, Patrick; Bellé, Robert (Frontiers in Genetics, 2014)
Fertilization of sea urchin eggs involves an increase in protein synthesis associated with a decrease in the amount of the translation initiation inhibitor 4E-BP. A highly simple reaction model for the regulation of protein synthesis was built and was used to simulate the physiological changes in the total 4E-BP amount observed during time after fertilization. Our study evidenced that two changes occurring at fertilization are necessary to fit with experimental data. The first change was an 8 fold increase in the dissociation parameter (koff1) of the eIF4E:4E-BP complex. The second was an important 32.5 fold activation of the degradation mechanism of the protein 4E-BP. Additionally, the changes in both processes should occur in five minutes time interval post fertilization. To validate the model, we checked that the kinetic of the predicted 4.2 fold increase of eIF4E:eIF4G complex concentration at fertilization matched the increase of protein synthesis experimentally observed after fertilization (6.6 fold, SD=2.3, n=8). The minimal model was also used to simulate changes observed after fertilization in the presence of rapamycin, a FRAP/mTOR inhibitor. The model showed that the eIF4E:4E-BP complex destabilization was impacted and, surprisingly, that the mechanism of 4E-BP degradation was also strongly affected, therefore suggesting that both processes are controlled by the protein kinase FRAP/mTOR.